P215 Patterns of respiratory co-morbidity and treatment strategies in inducible laryngeal obstruction and breathing pattern disorders. (12th November 2019) - Ludlow, SF; Somerton, C; Pantin, T; Haines, J; Fowler, S
Abstract : Background and aim: Patients are referred to our complex breathlessness service due to a clinical suspicion of Inducible Laryngeal Obstruction (ILO) and/or Breathing Pattern Disorder (BPD). We wanted to understand the prevalence of these disorders and their association with other respiratory co-morbidities. If a diagnosis was made we investigated if patients were seen for Speech and Language Therapy (SLT), Physiotherapy (PT), joint therapy or if their other respiratory diagnosis was treated first. Method: Data from all patients over a six month period who attended the Manchester Airways 'one stop day assessment' were analysed. Investigations included: full clinical history from SLT, PT, clinical nurse specialist, clinical psychologist and respiratory physician, a provocation laryngoscopy and lung function tests. Results: One hundred and fifty seven patients were seen in our complex breathlessness clinic between December 2018 and June 2019. Eighty-eight (56%) of these [67 female, median (range) 54 (17–83) years] had confirmed ILO (n=32), BPD (20) or both (36). Other relevant co-morbidities are shown in table 1. Of the patients diagnosed with ILO, most occurred on inspiration (91%) and at the glottic level (87%). All six patients with a diagnosis of tracheobronchomalacia also had a BPD. The majority of patients with a diagnosis of COPD were diagnosed with a BPD (6/7, 86%); with a high proportion also having expiratory ILO (3/7, 43%). A high percentage of patients had concurrent diagnoses of asthma, ILO and BPD (28%). Of the patients diagnosed with ILO, BPD or both; 46 were referred for SLT (52%), 20 for PT (23%) and 15 for joint SLT and PT (17%). Seven of the patients were not given therapy due to other co-morbidities needing to be medically managed first. Eight patients (9%) were referred for clinical psychology on this initial visit. Conclusion: A high proportion of patients referred to the complex breathlessness service received a diagnosis of ILO and/or BPD, and many also had a diagnosis of asthma or other respiratory disease. Few were referred for clinical psychology at the initial assessment, but these issues are often discussed during SLT/PT sessions and referrals made at a later date.